Such an unsimple "simple" patient with heart failure: constrictive pericarditis: case report - V. V. Vankhin; Yu. V. Ilyina; M. K. Rybakova; T. A. Fedorova; S. Ya. Tazina; T. I. Sotnikova; N. V. Semenenko; N. V. Loshchits; Ch. S. Pavlov (Кардиоваскулярная терапия и профилактика)
Constrictive pericarditis (CP) is a rare disease with various causes. At the end of the 20th century, its etiology was often associated with tuberculosis, but recently the role of cardiac surgery has increased in developed countries. CP is difficult to diagnose due to the lack of specific manifestations. The disease is characterized by symptoms of systemic venous congestion due to impaired diastolic filling. In heart failure, pericardial calcification is often not detected on a chest X-ray, and the diagnosis is verified in clinical practice using Doppler echocardiography.Case report. A 60-year-old man was hospitalized in November 2020 with complaints of progressive shortness of breath, swelling of lower limbs, anterior abdominal wall, lower back, and an increase in abdominal volume. In 2012, coronary artery bypass grafting was performed for multivessel coronary artery disease. Since 2018, the above complaints have appeared. Clinical manifestations were assessed as the development of heart failure due to ischemic cardiomyopathy. The prescribed complex therapy did not give an effect, and shortness of breath and edema and ascites continued to progress. It was necessary to find out the cause of the increase in systemic venous congestion. Taking into account the medical history and physical examination, pulmonary embolism, heart defects, pericarditis, as well as extracardiac pathology were included in the diagnostic search. The diagnosis of CP was established on the basis of the clinical performance, echocardiography and chest computed tomography. In April 2021, the patient underwent pericardiectomy. Subsequently, clinical and paraclinical improvement was noted with the disappearance of shortness of breath, edema, and an increase in myocardial contractility.Conclusion. The rare occurrence of the disease, a long period without manifestations after cardiac surgery, non-specific symptoms and concomitant diseases led to a delayed diagnosis of CP. Its clinical feature is the complexity of diagnosis and the use of a single method of treatment (pericardiectomy), which improves the patient's prognosis.